HUBUNGAN ANTARA DERAJAT PENYAKIT GINJAL KRONIK DENGAN NILAI AGREGASI TROMBOSIT DI RSUP PROF. DR. R. D. KANDOU MANADO - Tandi, Melti; Mongan, Arthur; Manoppo, Firginia (e-Biomedik, 2014)
Abstract: Chronic kidney disease has got a lot of attention and more widely studied despite reached end stage renal failure, patients still live a long life witha fairly good quality of life although the prevalence is increases throughout the year. one of the circumstances in chronic kidney disease is uremia which is a clinical and laboratory syndrome that occurs inorgans. In uremia interference with platelet function, the production ofprostacyclinin blood vesselswould increase, and excessurea levels in blood would be a potential vasodilator and platelet aggregation antagonist. Methods: An analytic observational cross-sectional study. Samples were patients that diagnosed with chronic kidney disease at the Hospital Clinic of Nephrology-Hypertension Prof. Dr.R. D.Kandou Manado in December toFebruary 2014. Criteria included were patientsÂ  <80 years old and has been diagnosed with chronic kidney disease in this case had done a physical examination and investigations by doctors, using medical record of urea-creatinine and also a complete blood countand platelet aggregation in Prokita Laboratory Manado. Forstatistical analysisusedShapiro-Wilk testalsoPearsonCorrelationstest. Result: There were 20 patients with chronic kidney disease sampled in this study. It was found that there is a relationship between of urea-creatinine and aggregation results in trace ADP5(P=0.004) while the value ADP10 no significant correlation(P =0.399). Conclusion: In chronic kidney disease patients, urea-creatininewiththe value of platelet aggregation intrace ADP5had a relation ship while intrace ADP10 had not a relationship. Keywords: Chronic kidney disease, platelet aggregation.